2006
DOI: 10.1590/s1519-566x2006000600005
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal population dynamics in Lucilia eximia (Wiedemann) (Diptera: Calliphoridae)

Abstract: Neotropical Entomology 35(6):753-756 (2006) Dinâmica Populacional Sazonal em Lucilia eximia (Wiedemann) (Diptera: Calliphoridae) RESUMO -Neste estudo variações sazonais da fecundidade, tamanhos de asa e tíbia foram investigadas em populações naturais de Lucilia eximia (Wiedemann), na tentativa de determinar as alterações bionômicas da espécie, associadas à sazonalidade. Exemplares de L. eximia foram coletados mensalmente em Botucatu, SP, durante dois anos e as fêmeas adultas dissecadas para estimar a fecund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
(25 reference statements)
2
8
1
1
Order By: Relevance
“…In addition, the results from previous studies designed to investigate the variation of demographic parameters in natural populations of blowflies show a spectrum of parameter values compatible with the numbers used in this study (Reigada & Godoy 2005, Gião & Godoy 2006, Riback & Godoy 2008.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In addition, the results from previous studies designed to investigate the variation of demographic parameters in natural populations of blowflies show a spectrum of parameter values compatible with the numbers used in this study (Reigada & Godoy 2005, Gião & Godoy 2006, Riback & Godoy 2008.…”
Section: Discussionsupporting
confidence: 68%
“…Lucilia eximia requires at least twice its estimated value to exhibit changes, since its experimentally obtained fecundity was very low. Nevertheless, natural populations of this species show fecundity values significantly higher than the numbers found in laboratory, justifying the arbitrary change in the simulations (Gião & Godoy 2006).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The short interval between generations at high temperatures (Queiroz & Milwardde-Azevedo, 1991;Krüger et al, 2010) and the high predation capacity of C. albiceps are factors that can be affect the abundance of other Calliphoridae that colonizes ephemeral resources, such as L. eximia during the southern hemisphere summer. Models to check the influence of randomness on population fluctuations of C. albiceps and L. eximia, based on data of South American populations have shown that intrinsic factors such as predation are more important than the extrinsic (environmental factors) to explain the variation in the abundance of these two species (Godoy et al, 2001;Silva et al, 2003;Gião & Godoy, 2006). This observation supports the third explanation of Moretti et al (2008) and Krüger et al (2010) aforementioned and is supported by the observed data in southern Brazil to explain the antagonistic fluctuation of C. albiceps and L. eximia.…”
Section: Discussionmentioning
confidence: 99%